Answer:
Fibonacci series is given by
f(0)=0, f(1)=1, f(2)=1, f(3)=2, f(4)=3.....
As you can see using the above result
f(4)=f(3) + f(2),
f(3)=f(2) + f(1),
f(2)=f(1) + f(0)
Proceeding using same pattern
f(5)=f(4) + f(3)=3+2=5
f(6)=f(4) + f(5)=3+5=8
f(7)=f(6) + f(5)=8+5=13
f(8)=f(7) + f(6)=13+8=21
f(9)=f(8) + f(7)= 21+13=34
f(10)=f(9) + f(8)=34+21=55
...........................................
..........................................
f(n-2)=f(n-3) + f(n-4)
f(n-1)=f(n-2)+ f(n-3)
Similarly and finally we get using the same pattern we get, As given f(n)=f(n-1) + f(n-2).